Kebijakan Pemerintah Dalam Pengembangan Industri Halal Terhadap Pertumbuhan Ekonomi Di Indonesia - Yulia, Sandre; Desriani, Wiwit; Isnaini , Desi (Pakis Journal Institute, 2024)
This research examines Indonesia's potential to become a global halal industry leader, with a focus on four main sectors. Through qualitative analysis, this research identifies the opportunities and challenges faced by Indonesia in building a strong halal ecosystem. Data are taken from previous studies and related literature. The goal is to provide a comprehensive overview of the halal industry in Indonesia as a basis for further research. This research was carried out through several stages. The first stage is a preliminary study to identify problems and phenomena related to the halal industry in Indonesia. The second stage is a conceptual framework as the basis for analyzing the potential development of the halal industry both at the national and global levels. In the final stage, conclusions and recommendations are presented based on the findings of the research. The results show that Indonesia has great potential, but continuous efforts are needed to improve product quality, strengthen branding and expand export markets. The main challenges faced are the consistent implementation of halal standards, as well as tight competition with other halal producing countries. To overcome these challenges, there needs to be synergy between the government, business actors and the community in building a sustainable halal ecosystem.